Thermal and Electronic Conductivity in Normal and Superconducting Erbium Nickel Borocarbide (ErNi2B2C) - Habtamu Tesfaye (Advances in Materials Science and Engineering)
In this work, the total electronic energy, the electronic thermal conductivity, and the heat capacity of erbium nickel borocarbide, ErNi2B2C, in the normal and superconducting states are calculated using Boltzmann transport equations (BTEs) and energy dispersion relation function. Results from the electronic thermal conductivity versus temperature (T) are presented. From the result, electrical and thermal conductivity at low temperature obey the Wiedemann–Franz law. Moreover, at the normal state, the electronic thermal conductivity of ErNi2B2C is directly proportional to the temperature (T) and reaches its maximum (kink) at the transition temperature, Tc. After the superconducting transition temperature, the electronic thermal conductivity begin to decrease. The drop in electronic thermal conductivity beyond its peak (kink) value is due to the formation of energy gap and the absence of Cooper pairs.